Enhancing the immune stimulatory effects of cetuximab therapy through TLR3 signalling in Epstein-Barr virus (EBV) positive nasopharyngeal carcinoma. (2nd November 2018) - Tan, Louise Soo Yee; Wong, Benjamin; Gangodu, Nagaraja Rao; Lee, Andrea Zhe Ern; Kian Fong Liou, Anthony; Loh, Kwok Seng; Li, Hao; Yann Lim, Ming; Salazar, Andres M.; Lim, Chwee Ming
ABSTRACT: Cetuximab immunotherapy targeting the epidermal growth factor receptor (EGFR) has been used to treat nasopharyngeal cancer (NPC) with some success. Therefore, combining an immune adjuvant to boost the immune microenvironment may improve its clinical efficacy. Herein, we investigate the immune-stimulatory effects of Poly-ICLC (a TLR3 agonist) in enhancing cetuximab-based immunotherapy and correlate these responses with FcɣRIIIa (V158F) or TLR3 single nucleotide polymorphisms (SNPs- L412F and C829T) expressed on immune effector cells. We observed high levels of TLR3 mRNA in NPC cells; and both TLR3 and EGFR expression were unaffected by Poly-ICLC treatment. Cetuximab plus Poly-ICLC significantly enhanced NK-mediated ADCC through up-regulation of CD107a and Granzyme B expression. This effect was independent of FcɣRIIIa-V158F and TLR3-L412F or TLR3-C829T polymorphisms expressed on NK cells. Additionally, IFN-ɣ expression and secretion were doubled following cetuximab plus poly-ICLC treatment; compared to either treatment alone. This effect was independent of TLR3 polymorphisms. Consequentially, adaptive immune responses were also seen with increased DC maturation (CD83), co-stimulatory molecules expression (CD80 and CD86) and increased frequency of EGFR-specific CD8 + T cells following Poly-ICLC treatment. The percentage of CD80+ CD83+ and CD83+ CD86+ DC was highest in the Poly-ICLC plus cetuximab group, compared to either treatment alone. These results demonstrate the effectiveness of Poly-ICLC in enhancing both cetuximab-mediated innate and adaptive anti-tumor immunity against NPC, which is independent of FcɣRIIIa-158, TLR3-L412F or TLR3-C829T polymorphisms. Additionally, Poly-ICLC does not downregulate EGFR expression on NPC cells and hence, will not dampen cetuximab anti-tumor activity.